Disasters everywhere: The costs of business cycles reconsidered - Òscar Jordà; Moritz Schularick; Alan M. Taylor (Federal Reserve Bank of New York, 2020)
Business cycles are costlier and stabilization policies more beneficial than widely thought. This paper shows that all business cycles are asymmetric and resemble mini "disasters." By this we mean that growth is pervasively fat-tailed and non-Gaussian. Using long-run historical data, we show empirically that this is true for all advanced economies since 1870. Focusing on the peacetime sample, we develop a tractable local projection framework to estimate consumption growth paths for normal and financial-crisis recessions. Using random coefficient local projections we get an easy and transparent mapping from the estimates to the calibrated simulation model. Simulations show that substantial welfare costs arise not just from the large rare disasters, but also from the smaller but more frequent mini-disasters in every cycle. In postwar America, households would sacrifice more than 10 percent of consumption to avoid such cyclical fluctuations.
Keywords: E13; E21; E22; E32; 330; fluctuations; asymmetry; local projections; random coefficients; macroprudential policy; Konjunktur; Stabilisierungspolitik; Finanzmarktaufsicht; Wohlfahrtsanalyse; USA